2015
DOI: 10.1134/s2070050415010109
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous biocatalytic processes of vegetable oil interesterification to biodiesel

Abstract: The heterogeneous biocatalytic interesterification of vegetable oils to ethyl esters of fatty acids is studied. Interesterification with ethanol or ethyl acetate is performed using biocatalysts obtained by incorpo rating cell lysates of the rE. coli/lip recombinant strain that produces thermostable Thermomyces lanuginosus lipase, into silica xerogel. The interesterification of vegetable oils is performed in both a batch stirred tank reactor and a continuous reactor with a fixed bed of the prepared biocatalyst.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…2). It is known that ethanol can inactivate various enzymes, including immobilized rPichia/lip [29]. Since the hydrophobicity of the original MCA in the presence of ethanol significantly decreased due to adsorption of ethanol molecules on CNTs, this adsorbent was apparently capable of exhibiting a protective effect by reducing the local concentration of C 2 H 5 OH in the lipase microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…2). It is known that ethanol can inactivate various enzymes, including immobilized rPichia/lip [29]. Since the hydrophobicity of the original MCA in the presence of ethanol significantly decreased due to adsorption of ethanol molecules on CNTs, this adsorbent was apparently capable of exhibiting a protective effect by reducing the local concentration of C 2 H 5 OH in the lipase microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…In reaction (III), the reaction medium consisted of 0.1 mol/L vegetable (sunflower or linseed) oil, 1.85 mol/L methyl acetate or dimethyl carbonate or 2.3 mol/L ethyl acetate, and a solvent (hexane). Transesterification products were identified by thin layer chromatography (TLC), as was described in our earlier publication [27]. The tributyrin hydrolysis and ester synthesis rates were determined by acid-base titration from the increase and decrease in the concentration of butyric acid and capric acid, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…6a). Earlier [27,28], we demon strated that one of the causes of the inactivation of bio catalysts in reactions involving "oil" substrates is the dehydration of adsorbed lipase as a result of triglycer ides displacing "essential" water molecules from the microenvironment of the enzyme. For verifying this hypothetical inactivation mechanism, the biocatalysts were also examined in an esterification reaction, whose product is water.…”
Section: Preparation Of Lipase Active Biocatalystsmentioning
confidence: 99%
“…Below is authors' report of the most effective rE. coli/lip lysate-based biocatalysts prepared and studied in the following reactions: (1) hydrolysis of tributyrin [16,19]; (2) interesterification of oil-fat blends [16,19,36,40]; (3) interesterification of sun flower oil with ethyl acetate [40,41]; (4) esterification of fatty acid with aliphatic alcohols [36,42]. It was found that the rates of reactions were considerably in more than 500 times higher in aqueous buffered media (hydrolysis) than in anhydrous organic solvents (esterification).…”
Section: Lipase-active Biocatalystmentioning
confidence: 99%
“…The interesterification of vegetable oil with methyl-or ethyl acetate was carried out in periodic mode in a stirred-tank reactor on a shaker at 120-150 rpm and 40 • C. The reaction medium had the following composition: 0.1 M oil, 2.3-2.5 M ethyl acetate, solvent-n-hexane. Depending on the activity of the prepared biocatalyst, the duration of one reaction cycle ranged from 5 to 144 h. The products-ethyl esters of fatty acids-were analyzed using gas (GC) and thin-layer chromatography (TLC) under the conditions described elsewhere [41].…”
Section: Interesterification Of Vegetable Oil With Ethyl Acetatementioning
confidence: 99%